2016
DOI: 10.1016/j.soilbio.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Beyond microbes: Are fauna the next frontier in soil biogeochemical models?

Abstract: The explicit representation of microbial communities in soil biogeochemical models is improving their projections, promoting new interdisciplinary research, and stimulating novel theoretical developments. However, microbes are the foundation of complicated soil food webs, with highly intricate and non-linear interactions among trophic groups regulating soil biogeochemical cycles. This food web includes fauna, which influence litter decomposition and the structure and activity of the microbial community. Given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 63 publications
2
85
0
2
Order By: Relevance
“…Several studies indicated density-dependent relationship between soil mesofauna and microbial biomass (González et al 2001; Lenoir et al 2007;Crowther and A'Bear 2012). This fauna-microbe interactions are exhibited in the current soil biogeochemical models (Grandy et al 2016). Nonetheless, the soil mesofauna represent coarse groupings that do not take into account the fact that different soil organisms within the same size group could exhibit different life history strategies or physiological capabilities (Coleman et al 2004) and that their relative importance in performing a specific function could change across temporal and spatial scales.…”
Section: Resultsmentioning
confidence: 86%
“…Several studies indicated density-dependent relationship between soil mesofauna and microbial biomass (González et al 2001; Lenoir et al 2007;Crowther and A'Bear 2012). This fauna-microbe interactions are exhibited in the current soil biogeochemical models (Grandy et al 2016). Nonetheless, the soil mesofauna represent coarse groupings that do not take into account the fact that different soil organisms within the same size group could exhibit different life history strategies or physiological capabilities (Coleman et al 2004) and that their relative importance in performing a specific function could change across temporal and spatial scales.…”
Section: Resultsmentioning
confidence: 86%
“…However, accurately representing all the potential population processes in models would be a daunting and perhaps unnecessary exercise (Grandy et al . ). The important practical question to ask is which mechanisms are dominant determinants of microbial biomass, community composition, and/or physiological responses to environmental perturbations.…”
Section: Section 2: Ecological Assumptions Inherent In Current Biogeomentioning
confidence: 97%
“… as early examples; and Buchkowski ; Grandy et al . ; Soong & Nielsen for justification). Incorporating insights from developments in population ecology into biogeochemical models represents a new frontier for development of biogeochemical theory and prediction.…”
Section: Introductionmentioning
confidence: 99%
“…though recently there has been growing interest in attempting to describe the patterns (Grandy et al, 2016). Certain links among groups of organisms are relatively well established, particularly between plants and microbes.…”
Section: Introductionmentioning
confidence: 99%